WEWENANG PEMERINTAH DAERAH DALAM PENERTIBAN PEREDARAN MINUMAN KERAS DI KOTA CILEGON: Cilegon's City Government Authority On Liquor Distribution Curbing - Rafly Tri Adi; Wiratno (Faculty of Law, Universitas Trisakti, 2024)
The Cilegon City Government has prohibited the sale of alcoholic drinks with an alcohol content above 10%. The impacts of selling alcoholic beverages include social inequality, increased alcohol-related crime, and risks to future generations. The problem formulation in this research focuses on local government policies regarding the challenges faced by officers in controlling alcohol distribution, and how the government overcomes these challenges. The research method uses normative legal methods, descriptive analysis, and data collection through interviews, observation, and documentation studies, with primary and secondary data. Conclusions are drawn deductively. The results of the research and discussion show that based on Article 18 which states